2020
DOI: 10.1096/fj.202000180rr
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein T protects against cisplatin‐induced acute kidney injury through suppression of oxidative stress and apoptosis

Abstract: Previously, selenoprotein T (SelT) expression was shown to be induced in nervous, endocrine, and metabolic tissues during ontogenetic and regenerative processes. However, whether SelT plays a critical role in renal diseases remains unclear. Here, we explored the role of SelT in cisplatin‐induced acute kidney injury (AKI). Results revealed that SelT was highly expressed in renal tubules, but its expression was significantly reduced in cisplatin‐induced AKI. Importantly, knocking down of SelT expression in kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…As an essential ER protein, SELENOT is required for adaptation in stressful conditions like unfolded protein response [58,59]. It was shown to have protective effects in an ischemia-reperfusion model [84] and may suppress oxidative stress and apoptosis [85]. Since ER stress and proteotoxicity are involved in the molecular pathology of cardiac dysfunction [86], reducing it may be favorable.…”
Section: Protein Folding and Er Stressmentioning
confidence: 99%
“…As an essential ER protein, SELENOT is required for adaptation in stressful conditions like unfolded protein response [58,59]. It was shown to have protective effects in an ischemia-reperfusion model [84] and may suppress oxidative stress and apoptosis [85]. Since ER stress and proteotoxicity are involved in the molecular pathology of cardiac dysfunction [86], reducing it may be favorable.…”
Section: Protein Folding and Er Stressmentioning
confidence: 99%
“…Moreover, this regimen resulted in stress injuries [ 33 ]. In addition, SELENOT protects kidney cells against cisplatin-induced apoptosis [ 34 ]. These observations go along with the notion that ER-resident selenoproteins are critical in cellular stress responses [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that SELENOT could protect dopaminergic neurons in mouse models of Parkinson's disease because of its crucial oxidoreductase activity [9]. In a recent study, Selenot knockdown aggravated cisplatin-induced apoptosis in NRK-52E cells, a kind of rat renal tubular epithelial cells, indicating that SELENOT prevented mice from cisplatin-induced acute kidney injury (AKI) by suppressing oxidative stress and cell apoptosis [20]. However, the function of SELENOT remains little known.…”
Section: Discussionmentioning
confidence: 99%